Magnetic localization and manipulation of locking synchronous motors - Michiel Richter; Lukas Masjosthusmann; Pavlo Makushko; Venkatasubramanian Kalpathy Venkiteswaran; Denys Makarov; Sarthak Misra (Communications Engineering)
Abstract Three-dimensional (3D) localization of magneto-surgical devices is essential for safe and efficient navigation. However, existing magnetic localization methods either limit device miniaturization due to internal sensors or require additional excitation fields and external sensor arrays. Herein, we formulate a localization method based on the special properties of rotating magnetic dipoles, which allow reconstruction of position and rotation axis from a single external tri-axial magnetometer. The rotating dipole is realized through a permanent magnet synchronous motor (PMSM) that can reversibly (un)lock using the heat-induced phase transition of a low melting point alloy. Sequential localization and manipulation is performed by an external mobile electromagnet equipped with a single eye-in-hand Hall effect sensor. We describe the PMSM’s thermal and magnetic properties, formulate the governing localization equations, quantify and validate 3D tracking of PMSM pose trajectory, and demonstrate sequential localization and manipulation in a benchtop experiment.